Establishment of Myotis myotis cell lines--model for investigation of host-pathogen interaction in a natural host for emerging viruses - He, Xiaocui; Korytář, Tomáš; Zhu, Yaqing; Pikula, Jiří; Bandouchova, Hana; Zukal, Jan; Köllner, Bernd (PloS one, 2014)
Bats are found to be the natural reservoirs for many emerging viruses. In most cases, severe clinical signs caused by such virus infections are normally not seen in bats. This indicates differences in the virus-host interactions and underlines the necessity to develop natural host related models to study these phenomena. Due to the strict protection of European bat species, immortalized cell lines are the only alternative to investigate the innate anti-virus immune mechanisms. Here, we report about the establishment and functional characterization of Myotis myotis derived cell lines from different tissues: brain (MmBr), tonsil (MmTo), peritoneal cavity (MmPca), nasal epithelium (MmNep) and nervus olfactorius (MmNol) after immortalization by SV 40 large T antigen. The usefulness of these cell lines to study antiviral responses has been confirmed by analysis of their susceptibility to lyssavirus infection and the mRNA patterns of immune-relevant genes after poly I:C stimulation. Performed experiments indicated varying susceptibility to lyssavirus infection with MmBr being considerably less susceptible than the other cell lines. Further investigation demonstrated a strong activation of interferon mediated antiviral response in MmBr contributing to its resistance. The pattern recognition receptors: RIG-I and MDA5 were highly up-regulated during rabies virus infection in MmBr, suggesting their involvement in promotion of antiviral responses. The presence of CD14 and CD68 in MmBr suggested MmBr cells are microglia-like cells which play a key role in host defense against infections in the central nervous system (CNS). Thus the expression pattern of MmBr combined with the observed limitation of lyssavirus replication underpin a protective mechanism of the CNS controlling the lyssavirus infection. Overall, the established cell lines are important tools to analyze antiviral innate immunity in M. myotis against neurotropic virus infections and present a valuable tool for a broad spectrum of future investigations in cellular biology of M. myotis.
Keywords: interakce hostitele a patogenu; buněčné linie; Immunity, Innate; Organ Specificity; Host-Pathogen Interactions; Animals; Cell Line; mužské pohlaví; Male; viry; orgánová specificita; Chiroptera; zvířata; přirozená imunita; Viruses